KHALED HOSSEINI AND COMPRADOR NARRATION - RAMESH, REVA; B , MEENU (International Journal of Psychosocial Rehabilitation, 2020)
Home is where your comfort lays, a place where one can connect to ones roots. But for refugees, what does home imply? How hard it will be to leave one’s place of birth and move to another land where everything seems other. Thousands of people have lost their lives in their effort to cross the borders and to find a new home and safety. Often people will get used to their new home, new culture, but one can always find a sense of longing for culture, religion and tradition offered by the homeland as it defines what we are. Unable to cope up with their new life, people choose to return to their war torn home where, language and employment will never be a problem. This paper deals with the category of refugee writing in literature and how such writing goes in parallel with the real life incidents of writers such as Khaled Hosseini